2012
DOI: 10.1136/bcr.03.2012.6134
|View full text |Cite
|
Sign up to set email alerts
|

An unusual bump on the head. Intraextracranial meningioma presenting incidentally

Abstract: Meningiomas are common intracranial tumours which rarely extend to extra cranial sites. Here, the authors report a rare case of an intracranial meningioma with extracranial spread into the subcutaneous tissues of the scalp, with a brief overview of the literature. An 82-year-old man presented following a fall. At the time of assessment, it was noted that he had a large deformity over the frontal area of his scalp. It was unclear as to the duration of this deformity. Following an inconclusive CT head he underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Owing to the similar results from immunohistochemical staining of type II and III meningiomas, imaging involving a combination of x-ray and MRI or CT and MRI was performed to appropriately classify the tumors. 27,37,38,[40][41][42][43] Based on our findings, both x-rays and CTs were unable to show the presence of intracranial exchange, resulting in MRIs being the recommended imaging technique to determine whether a lesion is dural based. 37,38,41…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the similar results from immunohistochemical staining of type II and III meningiomas, imaging involving a combination of x-ray and MRI or CT and MRI was performed to appropriately classify the tumors. 27,37,38,[40][41][42][43] Based on our findings, both x-rays and CTs were unable to show the presence of intracranial exchange, resulting in MRIs being the recommended imaging technique to determine whether a lesion is dural based. 37,38,41…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas have been described as extending into the subcutaneous tissue due to trauma, 15 bony defects in the skull, 16 through transdiploic extension via the venous valves, or through a calvarial foramen. 2 A list of other WHO grade II or higher cutaneous meningioma with scalp involvement is illustrated in Table 2. We theorize that this patient's type III lesion was directly influenced by the stage and osteolytic nature of the primary tumor.…”
Section: Case Studymentioning
confidence: 99%
“…Extracranial manifestations of meningiomas are rare. Patients may lack clinical findings such as headache or focal neurologic findings, but pathologic examination usually plays a major role in making this unusual diagnosis, which can be further supported by imaging 2 . Three distinct clinicopathological groups have been recognized for cutaneous meningiomas: congenital (type I), ectopic from the arachnoid tissue in the skin (type II), or from a direct extension from an intracranial meningioma (type III).…”
Section: Introductionmentioning
confidence: 99%
“…CT was suggestive of an exostosis and an enostosis associated with frontal skull thickening. The mass was excised, and its histological features were consistent with intraosseous meningioma [ 4 ]. Nadarajan et al [ 4 ] reported a similar case of unusual meningioma.…”
mentioning
confidence: 99%
“…The mass was excised, and its histological features were consistent with intraosseous meningioma [ 4 ]. Nadarajan et al [ 4 ] reported a similar case of unusual meningioma. An 82-year-old man was had a large deformity over the frontal area of his scalp.…”
mentioning
confidence: 99%